2021
DOI: 10.1097/ijg.0000000000001905
|View full text |Cite
|
Sign up to set email alerts
|

Early Experience With Full-scope Shared-care Teleglaucoma in Canada

Abstract: Précis: Large Canadian full-scope, shared-care teleglaucoma facilitates efficient management and diversion of medically stable patients away from overburdened subspecialty clinics while allowing patients the convenience of shorter travel, shorter wait time, and continuity with one provider. This report shares Care1 protocol, early patient characteristics, and quality data.Purpose: This paper describes early experience with Care1, a large full-scope, shared-care teleglaucoma program. Optometrists located in hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…32 More recently, an early experience with Care1, a large full-scope, shared-care teleglaucoma program in Canada, was reported. 33 Optometrists located in high-demand locations saw patients in person, acquired clinical history, performed a physical examination, organized diagnostic testing, then uploaded data to a proprietary online platform where they were able to collaborate with participating ophthalmologists to make plans for patient care. 33 A teleglaucoma initiative was also implemented at a Veterans Affairs Hospital in Pittsburgh, where a pilot study was aimed to evaluate the reliability and efficacy of a remote patient monitoring teleglaucoma initiative in a veteran population.…”
Section: Teleglaucoma For Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…32 More recently, an early experience with Care1, a large full-scope, shared-care teleglaucoma program in Canada, was reported. 33 Optometrists located in high-demand locations saw patients in person, acquired clinical history, performed a physical examination, organized diagnostic testing, then uploaded data to a proprietary online platform where they were able to collaborate with participating ophthalmologists to make plans for patient care. 33 A teleglaucoma initiative was also implemented at a Veterans Affairs Hospital in Pittsburgh, where a pilot study was aimed to evaluate the reliability and efficacy of a remote patient monitoring teleglaucoma initiative in a veteran population.…”
Section: Teleglaucoma For Monitoringmentioning
confidence: 99%
“…For patients with positive screening for glaucoma based on virtual assessment, face-to-face consultation was scheduled, and hypotensive ocular medication started in most cases 32. More recently, an early experience with Care1, a large full-scope, shared-care teleglaucoma program in Canada, was reported 33. Optometrists located in high-demand locations saw patients in person, acquired clinical history, performed a physical examination, organized diagnostic testing, then uploaded data to a proprietary online platform where they were able to collaborate with participating ophthalmologists to make plans for patient care 33…”
Section: Teleglaucomamentioning
confidence: 99%
“…In ophthalmology, telemedicine is well-validated and widely accepted in diabetic retinopathy screening [1], and more recently has found traction in glaucoma monitoring [2][3][4][5], retinopathy of prematurity screening [6,7], macular degeneration screening [8,9], and comprehensive ophthalmology [10]. Increasingly inexpensive and ubiquitous technologies, expanding computational power, and surging demand for limited healthcare resources are all pressures that have contributed its popularity.…”
Section: Introductionmentioning
confidence: 99%
“…We have read with interest the paper "Early Experience With Full-scope Shared-care Teleglaucoma in Canada" by Elson et al 1 We found it very relevant to the current literature due to the great global burden of glaucoma and the relevance that telemedicine has taken during the COVID-19 pandemic. The integration of the available technology with the adequate flow of patients will necessarily result in better screening opportunities and will reduce the barriers to access to health care services.…”
mentioning
confidence: 96%
“…This is critical in tele-ophthalmology programs like the one reported here, as there is evidence of different adherence rates between patients receiving usual care versus enhanced interventions, not only in glaucoma 3 but also in other diseases such as diabetic retinopathy. 4,5 Studies such as the one carried out by Elson et al, 1 are very important both to analyze the methods currently used in face-to-face practices and to implement and scale up tele-ophthalmology. In this way, a greater reach can be achieved for these promising remote services that are gaining more and more strength.…”
mentioning
confidence: 99%